72 Years of Homemaking in Waiting Zones: Lebanon's “Permanently Temporary” Palestinian Refugee Camps - El Masri, Yafa (Frontiers in Sociology, 2020)
The “permanently temporary” Palestinian refugee community, present in Lebanon since 1948 with no solution in sight, has the highest rate of abject poverty within all five areas of operation of United Nations Relief and Works Agency for Palestinians in the Near East (UNRWA), and it still occupies the same limited geographic space it did 72 years ago. This harsh reality stems from the refugees’ statelessness but is also worsened by the local conditions imposed by the Lebanese legislation and (non)settlement policy aimed at preventing refugees from becoming permanent. Within this situation, we look at practices of agency enacted by camp dwellers to provide lacking life necessities and improve living conditions in the camps. This paper will identify and analyze coping mechanisms and homemaking practices undertaken by Palestinian refugees in Lebanon, operating within the framework set by Anita Fábos and Cathrine Brun (2015), which conceptualized home and homemaking for people in protracted displacement through identifying a refugee’s “home, Home and HOME”. Building on Donna Haraway’s concept of situated knowledge, this paper uses data collected from participant observations, interviews, ethnographic and autoethnographic recordings analyzed through the lens of my own positioned rationality as a Palestinian refugee from Lebanon. Further, the paper will explore how Palestinian refugees establish camp spaces as a “home-Home-HOME”, despite their uncertain futures, through vertical expansion of buildings, stories and family bonding, in addition to trading and micro-markets. The paper will also deduce how refugees’ informal coping mechanisms offer a way of strengthening community bonds, making home in those, otherwise, uncomfortable “waiting zones,” and finally, envisioning new ideas for restructuring the camp beyond the rule of formal institutions.